2014
DOI: 10.1097/jsm.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Tackle

Abstract: Jejunal perforation as a result of blunt abdominal trauma during sport is particularly rare. We are aware of 6 reported cases of jejunal perforation in sport: 1 in hockey, 2 in football (soccer), and 3 in American football. This report presents the case of a 25-year-old professional rugby union player, who presented to an "After Hours" general practice clinic with increasing central abdominal and epigastric pain after a heavy tackle during an international match in New Zealand. Despite suffering complete jejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Most cases of small bowel perforations after blunt trauma occur as a result of motor vehicle crashes and falls from heights, and associated with multiple injuries. To the best of our knowledge, there have been only three reported cases of isolated jejunal transection following blunt abdominal trauma (bicycle handle bar, soccer, rugby) [2] , [3] making this case the first report of isolated, complete transection of the jejunum following a motor vehicle crash, with the longest delay in presentation reported in literature. The only similar report found was of a complete jejunal transection presenting 3 h post injury after a rugby game [2] .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Most cases of small bowel perforations after blunt trauma occur as a result of motor vehicle crashes and falls from heights, and associated with multiple injuries. To the best of our knowledge, there have been only three reported cases of isolated jejunal transection following blunt abdominal trauma (bicycle handle bar, soccer, rugby) [2] , [3] making this case the first report of isolated, complete transection of the jejunum following a motor vehicle crash, with the longest delay in presentation reported in literature. The only similar report found was of a complete jejunal transection presenting 3 h post injury after a rugby game [2] .…”
Section: Introductionmentioning
confidence: 83%
“…Delayed presentation may occur if the bowel is not ruptured immediately and in such cases, sepsis may develop with increased mortality [6] . Complete jejunal transection presenting 3 h post injury after a rugby game has been reported [2] . Repeated studies have shown increased mortality rates to be directly related to delay in diagnosis [3] .…”
Section: Discussionmentioning
confidence: 99%